(untitled) (Journal of Social Sciences Review, 2025)
The current study was conducted to identify the relationship between selfies and narcissism and the impact of narcissism on selfie-taking and posting behavior. It also attempts to find out gender differences in these two variables among the undergraduate students of Peshawar. Narcissism is defined as an exaggerated sense of one’s own importance and lack of empathy towards others. Selfies are defined as photographs of yourself that you click with smart phone. The age range of the sample was 18-25. Simple random sampling was used, a sample of 200 (100 males and 100 females) from five private universities in Peshawar was selected. The Narcissistic personality inventory (NPI) and a demographic and informed consent sheet were administered. Statistical analysis through Pearson correlation revealed that there is a significant relationship between selfies and regression analysis revealed that narcissism has a confirmed impact on selfie behavior. Through the t-test, it was elaborated that male students are higher in both selfies and narcissism. The results of the study supported the proposed hypotheses. Future researchers may explore the impact of spirituality, religiosity, and mental health issues on selfie behavior and narcissism. Additionally, investigating effective therapies for individuals severely affected by narcissism related to selfie-taking is recommended.